Efektivitas Implementasi Peraturan Wali Kota Nomor 32 Tahun 2020 di Taman Margasatwa dan Budaya Kinantan Kota Bukittinggi - Nafi, Rihadatun; Khaidir, Afriva (Policy, Law and Political Research Center, 2024)
The research aims to describe how effectiva the implementation of Mayor's Regulation no. 32 of 2020 is in the Kinantan Wildlife and Cultural Park, Bukittinggi City (TMSBK). It started with problems when implementing non-cash only which was implemented by the Bukittinggi City Government for access to TMSBK so that after an assessment was carried out the Bukittinggi City Government issued Mayor Regulation number 32 of 2020 concerning Procedures for Implementing the Collection, Payment, Deposit and Place of Payment of Recreational Retribution Retributions and Sports in an effort to overcome the problems felt by the people of Bukittinggi City by allowing cash and non-cash payments. This research uses qualitative research with descriptive methods supported by interview results. The data collection techniques used were observation, interviews and documentation studies. The validity test uses triangulation techniques, namely method triangulation and source triangulation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The research results show that the regulations implemented in TMSBK answer the problems felt by the people of Bukittinggi City, with these regulations people can carry out cash and non-cash transactions and this has an impact on levies which are directly proportional to the increase in the number of visits after this regulation is implemented. This regulation is certainly an effective solution to overcome the problems faced.